2021
DOI: 10.1101/2021.03.05.434000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of amyloid formation of the Nucleoprotein of SARS-CoV-2

Abstract: The SARS-CoV-2 Nucleoprotein (NCAP) functions in RNA packaging during viral replication and assembly. Computational analysis of its amino acid sequence reveals a central low-complexity domain (LCD) having sequence features akin to LCDs in other proteins known to function in liquid-liquid phase separation. Here we show that in the presence of viral RNA, NCAP, and also its LCD segment alone, form amyloid-like fibrils when undergoing liquid-liquid phase separation. Within the LCD we identified three 6-residue seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 64 publications
1
30
0
Order By: Relevance
“…In this study, we showed that the SARS-CoV-2 N protein phase separates with nonspecific RNA sequences in vitro and the viscosity and shape of these condensates depend on the structure of the RNA substrate. Concurrent studies have shown that the SARS-CoV-2 N protein expressed in bacteria forms biomolecular condensates with RNA in vitro [8,31,36,38,46,54,56,63,[71][72][73][74]. We purified N protein from mammalian cells to recapitulate the posttranslational modifications that occur in infected human cells [10].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed that the SARS-CoV-2 N protein phase separates with nonspecific RNA sequences in vitro and the viscosity and shape of these condensates depend on the structure of the RNA substrate. Concurrent studies have shown that the SARS-CoV-2 N protein expressed in bacteria forms biomolecular condensates with RNA in vitro [8,31,36,38,46,54,56,63,[71][72][73][74]. We purified N protein from mammalian cells to recapitulate the posttranslational modifications that occur in infected human cells [10].…”
Section: Discussionmentioning
confidence: 99%
“…Phase-separated condensates can nucleate amyloid-like fibrils, the nucleation process being enhanced in droplets or gels due to local concentration increase effects. A recent example is provided by the SARS-CoV2 nucleocapsid protein that forms amyloids in phase-separated droplets [ 106 ]. In line with this, IDRs are known to form amyloid-like structures via the formation of hydrogels [ 87 , 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…N‐NTR; 28–30, 35–184) had 34 matching structures, of which two were homotetramers, eight were homodimers, 14 were monomers, two showed binding to viral RNA, and one showed binding to an antibody. In addition, two structures matched to nine‐residue regions of N protein, showing these regions presented as epitopes by HLA (Szeto et al , 2021), while a final structure showed a six‐residue region assembled as an homo‐16‐mer that is implicated in amyloid formation (preprint: Tayeb‐Fligelman et al , 2021). The C‐terminal region (a.k.a.…”
Section: Resultsmentioning
confidence: 99%
“…The C‐terminal region (a.k.a. N‐CTR; 217–230, 243–365) had 22 matching structures, of which 16 were homodimers, four showed nine‐residue regions of N protein presented as epitopes by HLA (Szeto et al , 2021), and two showed six‐residue regions assembled as homo‐16‐mers that are implicated in amyloid formation (preprint: Tayeb‐Fligelman et al , 2021). These structures suggest the oligomerization and RNA‐binding activities of SARS‐CoV‐2 N protein may be disrupted by therapeutic strategies based on small molecule inhibitors developed for HCoV‐OC43 (human coronavirus OC43) and MERS‐CoV (Peng et al , 2020).…”
Section: Resultsmentioning
confidence: 99%